Political Accounting in Indonesia’s Strategic SOE IPO - Pratama, Obi (UNKLAB Business School, 2025)
Indonesia has increasingly turned to initial public offerings of strategic state-owned enterprises (SOEs) to finance post-pandemic development ambitions and showcase its climate credentials. The February 2023 listing of PT Pertamina Geothermal Energy (PGEO)—the country’s first geothermal-focused flotation—typifies this strategy, presenting the company as a flagship of the national green-transition agenda. This article investigates how accounting disclosures surrounding the IPO were mobilized as instruments of political legitimacy. Employing a mixed-methods design, the study combines systematic content analysis of the PGEO prospectus and 2022–2023 sustainability reports with an event study of abnormal share-price movements across an eleven-day (±5) window. The textual analysis uncovers a carefully layered narrative in which themes of “green leadership”, “energy sovereignty”, and “inclusive growth” are interwoven with governance affirmations to appeal simultaneously to investors, policy-makers, and civil society. The event study registers a cumulative abnormal return of approximately five per cent by day +2, indicating that markets provisionally validated the legitimacy signals embedded in the disclosures. Collectively, the findings suggest that PGEO’s IPO was orchestrated not merely as a capital-market transaction but as a calibrated act of political accounting aligning investor confidence with state objectives.